Alloy and preparation method thereof

By coating the titanium alloy powder and mixing it with the photosensitive resin, and using ultraviolet curing printing technology to prepare the alloy, the existing titanium alloy 3D printing technology has solved the problems of high energy consumption, large equipment costs and finished product defects, and achieved efficient, environmentally friendly and simple metal 3D printing.

CN119566325AActive Publication Date: 2025-03-07SOUTHERN UNIVERSITY OF SCIENCE AND TECHNOLOGY

Patent Information

Application Number
CN202411752463.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-07
Estimated Expiration
2044-12-02

AI Technical Summary

Technical Problem

The existing titanium alloy 3D printing technology has problems such as high energy consumption, high equipment costs and prone to defects in finished products.

Method used

The alloy powder is coated with a coating agent to form an alloy paste mixed with a photosensitive resin, a photoinitiator, and a dispersant, and then ultraviolet curing printing is performed to prepare the alloy.

Benefits of technology

It effectively avoids defects caused by difficult to accurately control the melting and solidification process of alloy powder in traditional methods, and is energy-saving and environmentally friendly, easy to operate, high efficiency and wide application range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119566325A_ABST
    Figure CN119566325A_ABST
Patent Text Reader

Abstract

The invention discloses an alloy and a preparation method thereof, and the preparation method comprises the following steps: carrying out coating treatment on alloy powder by adopting a coating agent, so that the viscosity of the alloy powder is 0.5-3 Pa.s, and obtaining coated alloy powder; mixing the coated alloy powder with photosensitive resin, a photoinitiator and a dispersing agent, and then carrying out ball milling treatment to obtain alloy slurry; and the alloy slurry is subjected to ultraviolet light curing printing treatment, and the alloy is obtained. The preparation method of the alloy provided by the invention has the following advantages: 1, energy conservation and environmental protection: 3D printing is carried out by adopting an ultraviolet curing mode, and compared with a traditional laser sintering or electron beam melting mode, high temperature is not needed, so that the energy consumption is greatly reduced, and meanwhile, the influence on the environment is also reduced; the 3D printing process can be carried out in the air, a vacuum or protective gas environment is not needed, operation is simpler and more convenient, and large-scale production is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of advanced manufacturing technology, and in particular to an alloy and a preparation method thereof. Background Art

[0002] Titanium alloys have low density, high strength, good corrosion resistance, stable high temperature performance, good mechanical properties and fatigue resistance, and are widely used in aerospace and biomedical fields. Additive manufacturing, that is, 3D printing technology, converts digital models into physical models by stacking layer by layer. Among them, titanium alloy 3D printing technology has received great attention due to its wide application in aerospace, biomedical, machinery manufacturing and other fields.

[0003] At present, the main means of titanium alloy additive manufacturing is to use laser beam, electron beam, arc, etc. as heat sources to melt or deposit titanium alloy powder to the target shape, and then stack it layer by layer to form. The existing titanium alloy additive manufacturing process mainly includes selective laser melting (SLM), selective laser sintering (SLS), electron beam selective melting (EBSM), wire-arc additive manufacturing (WAAM), etc. However, the above process methods all have limitations. For example: for selective laser melting (SLM) and selective laser sintering (SLS) with laser as heat source, it is necessary to prepare the raw material titanium alloy specific powder by gas atomization method and strictly screen it. At the same time, there are problems such as high laser power energy consumption, difficult to control printing accuracy, low molding efficiency, and high thermal stress of finished products during the printing process. For electron beam selective melting (EBSM) and wire-arc additive manufacturing (WAAM) with electron beam or arc as heat source, the printing process requires strict preheating of substrate temperature, control of atmosphere, etc., and the operation is relatively cumbersome. The finished products produced by the additive manufacturing process of titanium alloy melt molding will inevitably have defects such as dendrite growth, thermal cracks, and pores. At the same time, the equipment cost is high, making it difficult to carry out large-scale industrial production.

[0004] Therefore, the prior art still needs to be improved and developed. Summary of the invention

[0005] In view of the above-mentioned deficiencies in the prior art, the present invention provides an alloy and a preparation method thereof, so as to solve the problems of high energy consumption and high equipment cost of the existing metal 3D printing technology.

[0006] The technical solution adopted by the present invention to solve the above technical problems is as follows:

[0007] A first aspect of the present invention provides a method for preparing an alloy, the method comprising the following steps:

[0008] The alloy powder is coated with a coating agent so that the viscosity of the alloy powder is 0.5-3 Pa.s to obtain coated alloy powder;

[0009] The coated alloy powder is mixed with a photosensitive resin, a photoinitiator, and a dispersant, and then ball-milled to obtain an alloy slurry;

[0010] The alloy slurry is subjected to ultraviolet curing printing treatment to obtain the alloy.

[0011] Preferably, the alloy powder is titanium alloy powder, aluminum alloy powder, copper alloy powder or stainless steel powder.

[0012] Preferably, the coating agent is selected from one or more of styrene, acrylic acid, vinyl triethoxysilane, and methyl methacrylate.

[0013] Preferably, the step of coating the alloy powder with a coating agent is specifically as follows:

[0014] The alloy powder and the silane coupling agent are dissolved in ethanol and stirred, and then azobisisobutyronitrile and a coating agent are added in sequence under stirring to complete the coating treatment of the alloy powder.

[0015] Preferably, the mass ratio of the alloy powder, the silane coupling agent and the coating agent is (1:1:2)-(1:1:5).

[0016] Preferably, the photosensitive resin is selected from one or more of 1,6-hexanediol diacrylate, ethylene glycol dimethacrylate, acryloyl morpholine, trimethylolpropane triacrylate, and ditrimethylolpropane acrylate;

[0017] The photoinitiator is selected from one or more of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, diphenyl(2,4,6-triformyl)phosphine oxide, and 2,4,6-trimethylbenzoyl-di(p-tolyl)phosphine oxide;

[0018] The dispersant is selected from one or more of oleic acid, BYK-190, BYK-191, BYK-192 and BYK410 from BYK Chemical.

[0019] Preferably, the mass ratio of the coated alloy powder to the photosensitive resin is (5:3)-(10:3).

[0020] Preferably, the step of performing UV curing printing treatment on the alloy slurry specifically includes:

[0021] Place the alloy paste in the corresponding area of ​​the light-curing printer and set the printing parameters: the intensity of the ultraviolet light is 10-100mW / cm 2 , exposure time is 10-30s, layer thickness is 30-60μm, and the alloy is printed.

[0022] Preferably, after the alloy slurry is subjected to UV curing printing treatment, the method further comprises performing a degreasing treatment on the alloy embryo obtained after the UV curing printing treatment to remove excess moisture and photosensitive resin on the surface of the alloy embryo.

[0023] A second aspect of the present invention provides an alloy, wherein the alloy is prepared by the above-mentioned preparation method.

[0024] Beneficial effects:

[0025] The present invention discloses an alloy and a preparation method thereof. The preparation method of the alloy provided by the present invention has the following advantages: 1. The alloy slurry of the present invention comprises a photosensitive resin and a coated alloy powder, which can effectively avoid the defects caused by the difficulty in accurately controlling the melting and solidification process of the alloy powder in the traditional method, such as high porosity, uneven structure and the like. 2. Energy saving and environmental protection: The present invention adopts ultraviolet light curing to perform 3D printing. Compared with the traditional 3D printing methods such as laser sintering or electron beam melting, high temperature is not required, which greatly reduces energy consumption and also reduces the impact on the environment. 3. Simple operation: The 3D printing process of the present invention can be carried out in the air without vacuum or protective gas environment, which is more simple to operate and is conducive to large-scale production. 4. High efficiency: The ultraviolet light curing method of the present invention greatly improves the speed of model making, thereby improving the efficiency of metal 3D printing. 5. Wide application scope: The method of the present invention is not only applicable to titanium alloy materials, but also to high-strength alloys such as aluminum alloys, copper alloys, stainless steel, etc., thereby expanding the application scope of metal 3D printing technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The light-cured 3D-printed titanium alloy sample prepared in Example 1 of the present invention;

[0027] Figure 2 The roughness test result of the light-cured 3D printed titanium alloy prepared in Example 1 of the present invention;

[0028] Figure 3 The uniformity test results of the photocurable 3D printed titanium alloy prepared in Example 1 of the present invention: (a) is a scanning electron micrograph of the titanium alloy after sintering; (b) is a statistical graph of the grain size of the titanium alloy after sintering. DETAILED DESCRIPTION

[0029] The present invention provides an alloy and a preparation method thereof. To make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0030] An embodiment of the present invention provides a method for preparing an alloy, the method comprising the following steps:

[0031] The alloy powder is coated with a coating agent so that the viscosity of the alloy powder is 0.5-3 Pa.s to obtain coated alloy powder;

[0032] The coated alloy powder is mixed with a photosensitive resin, a photoinitiator, and a dispersant, and then ball-milled to obtain an alloy slurry;

[0033] The alloy slurry is subjected to ultraviolet curing printing treatment to obtain the alloy.

[0034] The preparation method of the alloy provided by the embodiment of the present invention has the following advantages: 1. The alloy slurry of the present invention includes a photosensitive resin and a coated alloy powder, which can effectively avoid the defects caused by the difficulty in accurately controlling the melting and solidification process of the alloy powder in the traditional method, such as high porosity, uneven organization and other problems. 2. Energy saving and environmental protection: The present invention adopts ultraviolet light curing for 3D printing. Compared with traditional 3D printing methods such as laser sintering or electron beam melting, high temperature is not required, which greatly reduces energy consumption and also reduces the impact on the environment. 3. Simple operation: The 3D printing process of the present invention can be carried out in the air without vacuum or protective gas environment, which is more convenient to operate and conducive to large-scale production. 4. High efficiency: The ultraviolet light curing method of the present invention greatly improves the speed of model making, thereby improving the efficiency of metal 3D printing. 5. Wide range of application: The method of the present invention is not only applicable to titanium alloy materials, but also to high-strength alloys such as aluminum alloys, copper alloys, stainless steel, etc., thereby expanding the application range of metal 3D printing technology.

[0035] In some embodiments, the alloy powder is coated with a coating agent so that the viscosity of the alloy powder is 1 Pa.s, thereby obtaining a coated alloy powder.

[0036] In some embodiments, the alloy powder is titanium alloy powder, aluminum alloy powder, copper alloy powder or stainless steel powder.

[0037] The method of the embodiment of the present invention is not only applicable to titanium alloy materials, but also to high-strength alloys such as aluminum alloys, copper alloys, stainless steel, etc., thereby expanding the application scope of metal 3D printing technology.

[0038] In some embodiments, the capping agent is selected from one or more of styrene, acrylic acid, vinyl triethoxysilane, and methyl methacrylate.

[0039] In some embodiments, the step of coating the alloy powder with a coating agent is specifically as follows:

[0040] The alloy powder and the silane coupling agent are dissolved in ethanol and stirred, and then azobisisobutyronitrile and a coating agent are added in sequence under stirring to complete the coating treatment of the alloy powder.

[0041] Coating the alloy powder can reduce the agglomeration of the alloy powder and increase the cured thickness. During the photocuring process, the difference in refractive index between the uncoated alloy powder and the photosensitive resin is too large, which reduces the cured thickness. After coating the surface of the alloy powder, the refractive index of the alloy powder surface is close to that of the resin, thereby increasing the cured thickness. Specifically, the alloy powder has hydroxyl groups, which react with the silane coupling agent, and then introduce azobisisobutyronitrile as an initiator and a coating agent to obtain the coated alloy powder. Among them, ethanol, as an environmental liquid, does not participate in the reaction, but can evenly disperse the alloy powder and the silane coupling agent to make them react more evenly.

[0042] In some embodiments, the mass ratio of the alloy powder, the silane coupling agent and the coating agent is (1:1:2)-(1:1:5).

[0043] If the ratio of silane coupling agent to coating agent is too small, the surface of alloy powder cannot be coated evenly, and if it is too much, it will cause waste.

[0044] In some preferred embodiments, the mass ratio of the alloy powder, the silane coupling agent and the coating agent is 1:1:3.

[0045] In some embodiments, the photosensitive resin is selected from one or more of 1,6-hexanediol diacrylate, ethylene glycol dimethacrylate, acryloyl morpholine, trimethylolpropane triacrylate, and ditrimethylolpropane acrylate;

[0046] The photoinitiator is selected from one or more of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, diphenyl(2,4,6-triformyl)phosphine oxide, and 2,4,6-trimethylbenzoyl-di(p-tolyl)phosphine oxide;

[0047] The dispersant is selected from one or more of oleic acid, BYK-190, BYK-191, BYK-192 and BYK410 from BYK Chemical.

[0048] In some embodiments, the mass ratio of the coated alloy powder to the photosensitive resin is (1:1:2)-(1:1:5).

[0049] In some preferred embodiments, the mass ratio of the coated alloy powder to the photosensitive resin is 10:3.

[0050] This ratio is the highest solid content that can be achieved at present. If the proportion of alloy powder increases, the solidification thickness will decrease, resulting in printing failure; if the proportion of alloy powder decreases, the shrinkage rate will increase during the sintering process, which is likely to bring greater shrinkage stress.

[0051] In some embodiments, the step of performing UV curing printing on the alloy slurry specifically includes:

[0052] Place the alloy paste in the corresponding area of ​​the light-curing printer and set the printing parameters: the intensity of the ultraviolet light is 10mW / cm 2 , exposure time is 10 s, layer thickness is 30 μm, and the alloy is printed.

[0053] In some embodiments, after the alloy slurry is subjected to UV-curing printing treatment, the method further includes degreasing the alloy embryo obtained after the alloy slurry is subjected to UV-curing printing treatment to remove excess moisture and photosensitive resin on the surface of the alloy embryo.

[0054] In some embodiments, the degreased metal body is further sintered.

[0055] After degreasing and sintering, a high-density alloy model is obtained, which can effectively avoid the defects caused by the difficulty in accurately controlling the melting and solidification process of the alloy powder in the traditional method, such as high porosity and uneven structure.

[0056] In some embodiments, a method for preparing an alloy is provided, the method comprising the following steps:

[0057] The alloy powder and the silane coupling agent are dissolved in ethanol in a mass ratio of 1:1, and stirred, and then azobisisobutyronitrile and a coating agent are added in sequence under stirring to obtain a coated alloy powder;

[0058] The coated alloy powder is mixed with a photosensitive resin, a photoinitiator, and a dispersant, and then ball-milled to obtain an alloy slurry;

[0059] Place the alloy paste in the corresponding area of ​​the light-curing printer and set the printing parameters: the intensity of the ultraviolet light is 50mW / cm 2 , the exposure time is 10s, the layer thickness is 30μm, printing is performed to obtain an alloy embryo body, and the alloy embryo body is degreased to remove excess moisture and photosensitive resin on the surface of the alloy embryo body to obtain the alloy.

[0060] A second aspect of the present invention provides an alloy, wherein the alloy is prepared by the above-mentioned preparation method.

[0061] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments, and are only for illustrating the present invention but not limiting the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.

[0062] Example 1

[0063] Step 1: D50 = 10 microns of Ti 6 Al 4 V powder and silane coupling agent KH570 were added to 300 mL ethanol solution at a ratio of 30 g:30 g, and the mixed liquid was stirred in a magnetic stirrer at 100 ° C for 3 hours. Then it was centrifuged in a centrifuge at 20000 r / min for 5 minutes, washed with ethanol and dried in a drying oven at 100 ° C for 48 hours. Then the treated titanium alloy powder (Ti 6 Al 4 V powder) was added to the butanone solution, and after ultrasonic dispersion, it was stirred in a magnetic stirrer at 70°C, and then 240 mg of azobisisobutyronitrile (AIBN) was added as an initiator. After 30 minutes, 15 mL of styrene was added dropwise, and the reaction was carried out at a speed of 350 r / min for 3 hours, and then centrifuged at 20000 r / min for 5 minutes, washed with ethanol and dried to obtain the coated Ti 6 Al 4 V powder.

[0064] Step 2: The coated Ti 6 Al 4 V powder (D50 = 10 μm) was mixed with 1,6-hexanediol diacrylate and trimethylolpropane triacrylate in a volume ratio of 45:45:10, and finally 2 wt.% of TPO photoinitiator and 2 wt.% of oleic acid dispersant were added based on the resin weight. The mixture was ball milled for 12 h at a rotation speed of 400 r / min to obtain alloy slurry.

[0065] Step 3: Place the alloy slurry into the 3D printer and set the printing parameters, including the intensity of the UV light to 10mW / cm 2 , exposure time is 10s, layer thickness is 30μm. Start the 3D printer to obtain the alloy embryo. The printer will solidify the alloy slurry layer by layer through UV curing according to the set parameters to form the required alloy model. In this process, the printer will accurately control the melting and solidification process of the alloy powder to avoid defects in the alloy model.

[0066] Step 4: Put the alloy body into the furnace for degreasing. The atmosphere in the furnace is argon. Raise the temperature to 200℃ at 2℃ / min, then to 300℃ at 1℃ / min, keep it warm for 120min, then to 500℃ at 0.5℃ / min, keep it warm for 300min, then to 800℃ at 8℃ / min, keep it warm for 30min, then to 1300℃ at 8℃ / min, keep it warm for 120min. At this point, the degreasing and sintering are completed, and a finely structured Ti is obtained. 6 Al 4 V structural parts, the actual Figure 1 .

[0067] The Ti prepared in Example 1 6 Al 4 V structural parts are tested for roughness and uniformity, see Figure 2 and Figure 3 ,Depend on Figure 2 It can be obtained that the Ti prepared in Example 1 6 Al 4 The roughness of the V-shaped structure is 3.61 μm, which is one order of magnitude smaller than that of laser printing. Figure 3 From (a) and (b), we can get Ti 6 Al 4 The grains of the V-structure are equiaxed grains with uniform grain size, mainly concentrated between 18-27μm, and the average grain size is 23.21μm. Compared with the long grains prepared by laser, equiaxed grains are beneficial to improving the mechanical properties of the material.

[0068] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.

Claims

1. A method for preparing an alloy, characterized in that: The preparation method comprises the following steps: The alloy powder is coated with a coating agent so that the viscosity of the alloy powder is 0.5-3 Pa.s to obtain coated alloy powder; The coated alloy powder is mixed with a photosensitive resin, a photoinitiator, and a dispersant, and then ball-milled to obtain an alloy slurry; The alloy slurry is subjected to ultraviolet light curing printing treatment to obtain the alloy.

2. The method for preparing the alloy according to claim 1, characterized in that: The alloy powder is titanium alloy powder, aluminum alloy powder, copper alloy powder or stainless steel powder.

3. The method for preparing the alloy according to claim 1, characterized in that: The coating agent is selected from one or more of styrene, acrylic acid, vinyl triethoxysilane, and methyl methacrylate.

4. The method for preparing the alloy according to claim 1, characterized in that: The steps of coating the alloy powder with a coating agent are specifically as follows: The alloy powder and the silane coupling agent are dissolved in ethanol and stirred, and then azobisisobutyronitrile and a coating agent are added in sequence under stirring to complete the coating treatment of the alloy powder.

5. The method for preparing the alloy according to claim 4, characterized in that: The mass ratio of the alloy powder, the silane coupling agent and the coating agent is (1:1:2)-(1:1:5).

6. The method for preparing the alloy according to claim 1, characterized in that: The photosensitive resin is selected from one or more of 1,6-hexanediol diacrylate, ethylene glycol dimethacrylate, acryloyl morpholine, trimethylolpropane triacrylate, and ditrimethylolpropane acrylate; The photoinitiator is selected from one or more of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, diphenyl(2,4,6-triformyl)phosphine oxide, and 2,4,6-trimethylbenzoyl-di(p-tolyl)phosphine oxide; The dispersant is selected from one or more of oleic acid, BYK-190, BYK-191, BYK-192 and BYK410 from BYK Chemical.

7. The method for preparing the alloy according to claim 1, characterized in that: The mass ratio of the coated alloy powder to the photosensitive resin is (5:3)-(10:3).

8. The method for preparing the alloy according to claim 1, characterized in that: The step of performing UV curing printing treatment on the alloy slurry specifically includes: Place the alloy paste in the corresponding area of ​​the light-curing printer and set the printing parameters: the intensity of the ultraviolet light is 10-100mW / cm 2 , exposure time is 10-30s, layer thickness is 30-60μm, and the alloy is printed.

9. The method for preparing the alloy according to claim 1, characterized in that: After the alloy slurry is subjected to UV curing printing treatment, the alloy blank obtained after the UV curing printing treatment is subjected to degreasing treatment to remove excess moisture and photosensitive resin on the surface of the alloy blank.

10. An alloy, characterized in that: The alloy is prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Photosensitive resin, preparation method thereof, ceramic slurry and 3D printing product

    CN109535333A

  • Photocuring 3D printing metal part and preparation method thereof

    CN112916868A

  • Photocuring stainless steel powder slurry

    CN115058137A

  • Aluminum alloy additive manufacturing method

    CN115815618A

  • Method for preparing metal ink and additive manufacturing based on photo-thermal synergistic curing

    US20240132733A1

Cited By

  • Laser melting resin doped with CdSnBiKC alloy powder and preparation method thereof

    CN120271944A

  • BiPbSnNaC alloy powder doped photosensitive resin and preparation method thereof

    CN120271945A